The AAT1 locus is critical for the biosynthesis of esters contributing to 'ripe apple' flavour in 'Royal Gala' and 'Granny Smith' apples. (23rd May 2014) - Souleyre, Edwige J. F.; Chagné, David; Chen, Xiuyin; Tomes, Sumathi; Turner, Rebecca M.; Wang, Mindy Y.; Maddumage, Ratnasiri; Hunt, Martin B.; Winz, Robert A.; Wiedow, Claudia; Hamiaux, Cyril; Gardiner, Susan E.; et al.
Summary The 'fruity' attributes of ripe apples (Malus × domestica) arise from our perception of a combination of volatile ester compounds. Phenotypic variability in ester production was investigated using a segregating population from a 'Royal Gala' (RG; high ester production) × 'Granny Smith' (GS; low ester production) cross, as well as in transgenic RG plants in which expression of the alcohol acyl transferase 1 (AAT1) gene was reduced. In the RG × GS population, 46 quantitative trait loci (QTLs) for the production of esters and alcohols were identified on 15 linkage groups (LGs). The major QTL for 35 individual compounds was positioned on LG2 and co‐located with AAT1. Multiple AAT1 gene variants were identified in RG and GS, but only two (AAT1‐RGa and AAT1‐GSa) were functional. AAT1‐RGa and AAT1‐GSa were both highly expressed in the cortex and skin of ripe fruit, but AAT1 protein was observed mainly in the skin. Transgenic RG specifically reduced in AAT1 expression showed reduced levels of most key esters in ripe fruit. Differences in the ripe fruit aroma could be perceived by sensory analysis. The transgenic lines also showed altered ratios of biosynthetic precursor alcohols and aldehydes, and expression of a number of ester biosynthetic genes increased, presumably in response to the increased substrate pool. These results indicate that the AAT1 locus is critical for the biosynthesis of esters contributing to a 'ripe apple' flavour.